Update on the management of ulcerative colitis: treatment and maintenance approaches focused on MMX® mesalamine. [Corrigendum] - Nanda K; Moss AC (Dove Medical Press, 2013)
Nanda K, Moss AC.Clinical Pharmacology: Advances and Applications. 2012, 4:41–50.The authors apologize for errors on Tables 1, 2, and 3.Table1Citation 40, Hussain et al, should have been citation 44, Shire US Inc.Table 2Lichtenstein et al data, the confidence interval (CI) of the odds ratio for achieving remission with MMX mesalamine 1.2 g twice daily (1.44–8.41) should be listed as a 97.5% CI rather than a 95% CI.Table 3Prantera et al, the MMX mesalamine 2.4 g once daily cohort should have an N value of 156, not 162, and the 12-month relapse rate should be 25.0%, not 15.0%.Pramtera et al, the Asacol 2.4 g once daily cohort should be labeled "Asacol 2.4 g/day twice daily", and should have an N value of 167, not 156.Kane et al, the N value should be 194, not 167.Read the original article